Light Response of CO(2) Assimilation, Dissipation of Excess Excitation Energy, and Zeaxanthin Content of Sun and Shade Leaves - Demmig-Adams, Barbara (1989)
Intact attached sun leaves of Helianthus annuus and shade leaves of Monstera deliciosa and Hedera helix were used to obtain light response curves of CO(2) uptake, the content of the carotenoid zeaxanthin (formed by violaxanthin de-epoxidation), as well as nonphotochemical quenching (q(NP)), and the rate constant of radiationless energy dissipation (k(D)). The latter two parameters were calculated from the decrease of chlorophyll a fluorescence at closed photosystem II traps in saturating pulses in the light. Among the three species, the light-saturated capacity of CO(2) uptake differed widely and light saturation of CO(2) uptake occurred at very different photon flux densities. Fluorescence quenching and zeaxanthin content exhibited features which were common to all three species: below light-saturation of CO(2) uptake nonphotochemical quenching occurred in the absence of zeaxanthin and was not accompanied by a decrease in the yield of instantaneous fluorescence. Nonphotochemical quenching, q(NP), increased up to values which ranged between 0.35 and 0.5 when based on a control value of the yield of variable fluorescence determined after 12 hours of darkness. As light saturation of CO(2) uptake was approached, q(NP) showed a secondary increase and the zeaxanthin content of the leaves began to rise. This was also the point from which the yield of instantaneous fluorescence began to decrease. The increase in zeaxanthin was paralleled by an increase in the rate constant for radiationless energy dissipation k(D), which opens the possibility that zeaxanthin is related to the rapidly relaxing “high-energy-state quenching” in leaves.